Pendampingan Pembuatan Perencanaan Bisnis Dan Pengembangan Usaha Kecil Di Kelurahan Cijengkol Bekasi - Untari, Dhian Tyas; Rianto, M Richo (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
The objectives of this Community Service activity are to; educating the Cijengkol village community about the procedure for applying for capital development credit, educating the Cijengkol village community about making business plans which are one of the requirements for applying for credit and assisting small entrepreneurs who want to develop their business in seeking business capital or business development capital . Activities are carried out by providing online training and offline assistance to the Cijengkol community. Mentoring activities are a series of ongoing activities, the community hopes that similar activities can be carried out intensively so that they can provide more tangible benefits.